Denial of human rights in Eastern Europe : the tenth anniversary of the Universal Declaration of Human Rights. (New York : Assembly of Captive European Nations (ACEN), 1958)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: anticommunisme; mensenrechten; Oost-Europa.